2018
DOI: 10.1038/s41598-018-28571-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of radioactivity by planar gamma-camera images, a promoted method of absorbed dose in the thyroid after iodine-131 treatment

Abstract: Iodine-131 (131I) is an essential and widely used radioisotope in thyroid diseases and animal experiments. Planar imaging has been considered the most popular method for 131I thyroid uptake radioactive activity quantification. The ROI defining section is essential and can affect the accuracy of quantitative results. However, a consistent method has not been proposed. In this study, a UC-ROI defining method based on ULWL setting and colour display grade was applied. Three steps were performed: image acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In recent years, with the advancement of the image processing field, a more precise ROI and background regions might be obtained, leading to more accurately quantifying planar imaging as well as reducing PVE. For example, [42] proposed a new technique to define the ROI boundary according to the upper limit window level and a ring-like shape of the background to correct ROI counts and obtain 131 I activity quantification in rat thyroid. The results were promising and revealed that using the above-mentioned method can lead to a more accurate 131 I quantification of thyroid uptake by SPECT planar imaging in an in-vivo rat study [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the advancement of the image processing field, a more precise ROI and background regions might be obtained, leading to more accurately quantifying planar imaging as well as reducing PVE. For example, [42] proposed a new technique to define the ROI boundary according to the upper limit window level and a ring-like shape of the background to correct ROI counts and obtain 131 I activity quantification in rat thyroid. The results were promising and revealed that using the above-mentioned method can lead to a more accurate 131 I quantification of thyroid uptake by SPECT planar imaging in an in-vivo rat study [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, [42] proposed a new technique to define the ROI boundary according to the upper limit window level and a ring-like shape of the background to correct ROI counts and obtain 131 I activity quantification in rat thyroid. The results were promising and revealed that using the above-mentioned method can lead to a more accurate 131 I quantification of thyroid uptake by SPECT planar imaging in an in-vivo rat study [42]. Regarding the great importance of choosing appropriate ROI in activity estimation, the values of ROI/size can be helpful for reducing PVE and consequently more accurate activity quantification in patient organs with different sizes, especially small organs.…”
Section: Discussionmentioning
confidence: 99%